John Short birthday
John Steinbeck, wearing shirt and tie, playing tug-o-war on occasion of picnic-barbecue for birthday of John Short, Senior, at Shorts's home on 45 hectares along coast. John and Carol visited the Shorts's home frequently. From left to right: John Short, Senior; Henry Williams (editor of Collier's); Major Morgan; Henry Dickinson (potter); John Short, Junior; JS, Wilfred Davis.